Association of portal venous system thrombosis with endoscopic variceal treatment: a systematic review and meta-analysis. Issue 2 (February 2021) - Wang, Le; Guo, Xiaozhong; Xu, Xiangbo; Philips, Cyriac Abby; Primignani, Massimo; Mendez-Sanchez, Nahum; Li, Qianqian; Zheng, Kexin; Qi, Xingshun
Abstract : The association of endoscopic variceal treatment (EVT) with the development of portal venous system thrombosis (PVST) in liver cirrhosis remains uncertain. A systematic review and meta-analysis aimed to investigate the incidence of PVST after EVT and to explore the association of EVT with the development of PVST in liver cirrhosis. All relevant studies were searched via the PubMed, EMBASE, and Cochrane Library databases. The incidence of PVST in patients treated with and without EVT was pooled. Risk ratios with 95% confidence intervals (CIs) were calculated. Heterogeneity among studies was calculated. Meta-regression, sensitivity, and subgroup analyses were used to analyze the source of heterogeneity. Thirteen studies involving a total of 833 patients were included. The pooled incidence of PVST after EVT was 10.4% (95% CI, 4.9–17.7%). There was a statistically significant heterogeneity ( I 2  = 83.3%, P  < 0.0001). Meta-regression, sensitivity, and subgroup analyses did not find the source of heterogeneity. Four studies compared the incidence of PVST between patients treated with and without EVT. The incidence of PVST was significantly higher in the EVT group than that in the no-EVT group (risk ratio: 2.23; 95% CI, 1.11–4.49; P  = 0.02). The heterogeneity was not statistically significant ( I 2  = 0%, P  = 0.43). In conclusion, PVST after EVT may not be scare, and EVT may increase the risk of PVST in liver cirrhosis. Abstract : Supplemental Digital Content is available in the text.